Capturing complex right ventricular wall motion abnormalities in arrhythmogenic right ventricular cardiomyopathy by combining longitudinal and radial myocardial dynamics in feature-tracking MRI. (8th February 2021) - Laredo, M; Lamy, J; Bouazizi-Verdier, K; Giron, A; Diallo, A; Gallo, A; Cluzel, P; Gandjbakhch, E; Redheuil, A; Kachenoura, N
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): INSERM Liliane Bettencourt doctoral grant Background: Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is associated with complex spatial and temporal right ventricular (RV) wall motion abnormalities. While cardiac magnetic resonance (CMR) is the gold-standard imaging technique, its diagnosic performance remains suboptimal and additional CMR biomarkers reflecting ARVC pathophysiology are needed. Purpose: To evaluate the performance of a CMR feature-tracking (FT)-derived parameter combining both longitudinal and radial RV deformation and motion for the characterization of RV wall motion abnormalities in ARVC. Methods: Thirty-nine patients with definite or borderline ARVC (median age 45 years, interquartile range 31–51, 56% males) were compared to 20 healthy controls with comparable age, sex and weight distributions. All subjects had 1.5T CMR including short axis and 4-chamber views steady-state free precession acquisitions. A custom FT software adapted to RV wall segmentation and tracking was used to assess RV wall deformation and motion in the 3 space directions resulting in: 1) global longitudinal strain (GLS) estimated on the 4 chamber view from the RV free wall, 2) basal circumferential strain (BCS) and radial motion fraction (BRMF) estimated as an average of short-axis slices comprised in the RV third basal portion. To capture the complex RV motion in ARCV, a longitudinal to radial strain loop (LRSL) was displayed and its area was calculated. Results: The ARVC group comprised 28 (72%) patients with definite and 11 (28%) with borderline diagnosis . As compared to controls, LVEF and RVEF were significantly lower in ARVC patients (61(interquartile range (IQR) 52-71) vs. 71%(IQR 55-88), p = 0.03 and 47%(IQR 16-63) vs. 57%(IQR 49-63), p = 0.02, respectively), LVEF remaining within normal range limits. While there was no significant difference in RV GLS between ARVC patients and controls (median -17.7%(IQR -24–15) vs. -17.5%(IQR -20.1–15.2), p = 0.67), BCS and BRMF were significantly lower in ARVC patients vs. controls [-7.5%(IQR -12.3–8.4.) vs. -9.8%(IQR -13.8–8.6.), p = 0.004 and -12.2(IQR -14.4–8.7.) vs. -14.9%(IQR -16.6–13.2) p = 0.0007, respectively] . The LRSL area was significantly and markedly lower in ARVC patients vs. controls [70.6 (IQR 16.3-63.1) vs. 144.1 (IQR 110.4-251.3), p = 0.0002] . LRSL area outperformed RVEF, BCS and BRS in separating ARVC from controls (area under receiving operator characteristics curve 0.82 vs. 0.78, 0.73 and 0.78, respectively). Conclusion: In ARVC, a FT-derived parameter combining longitudinal and radial RV wall deformation and motion provided better discrimination of ARVC patients from controls than conventional FT measurements. Its implementation in clinical practice may bolster CMR performance to characterize ARVC wall motion abnormalities.